Determinant Factors of Consumer Satisfaction in Syariah Hotels Service to Costumer Decision Impact - Adelia Putri Anzelina (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2024)
This research aims to find out the rate of consumer satisfaction regarding the decision to stay at a sharia hotel in North Sumatra. This research approach is quantitatif multivariance analysis. The population is all consumers and the sample is 100 consumers. In this research, the analysis was assisted by the SPSS 29.00 application using simple linear regression analysis to prove whether or not there was an impact provided by the independent variable on the dependent variable. The data analysis technique in this research uses the classic assumption test which includes the normality test, linearity test and heteroscedasticity test, and hypothesis testing which includes the t test.Â  To find out the coefficient of determination, a partial test will then be carried out to test the impact that the independent variable partially has on the dependent variable. Partially, the consumer satisfaction variable has a significant effect on decisions.Keywords: Sharia Hotel, Consumer Satisfaction, Decision to Stay